2020
DOI: 10.1039/d0cp02480e
|View full text |Cite
|
Sign up to set email alerts
|

Removal of H2S to produce hydrogen in the presence of CO on a transition metal-doped ZSM-12 catalyst: a DFT mechanistic study

Abstract: The Hydrogen Sulfide (H2S) leads to corrosion in transport lines and poisoning of many catalysts. Meanwhile, the H2S as inexhaustible potential source of hydrogen is very valuable chemical reagent and...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 74 publications
0
4
0
Order By: Relevance
“…Carbon-based nanomaterials, such as graphene (GN), graphyne, and heteroatom-doped carbon materials have been widely adopted as supports for SACs. [166][167][168] There has been a myriad of studies showing that the metal atoms doped carbon-based supports can realize significantly enhanced the reaction activities for removal of H 2 S. [52,[169][170][171][172] However, there are a few reviews works about the interaction between H 2 S and single atom supported catalyst from a theoretical perspective. Thus, in this review, we summarized three directions of removal of H 2 S on different single atom doped carbon-based supports: (i) Heteroatom (nitrogen, oxygen, sulfur, phosphor) doped GN carriers, (ii) Graphitic carbon nitride carriers, (iii) Mesoporous carbon nanotube carriers.…”
Section: Carbon-based Supports Sacsmentioning
confidence: 99%
See 1 more Smart Citation
“…Carbon-based nanomaterials, such as graphene (GN), graphyne, and heteroatom-doped carbon materials have been widely adopted as supports for SACs. [166][167][168] There has been a myriad of studies showing that the metal atoms doped carbon-based supports can realize significantly enhanced the reaction activities for removal of H 2 S. [52,[169][170][171][172] However, there are a few reviews works about the interaction between H 2 S and single atom supported catalyst from a theoretical perspective. Thus, in this review, we summarized three directions of removal of H 2 S on different single atom doped carbon-based supports: (i) Heteroatom (nitrogen, oxygen, sulfur, phosphor) doped GN carriers, (ii) Graphitic carbon nitride carriers, (iii) Mesoporous carbon nanotube carriers.…”
Section: Carbon-based Supports Sacsmentioning
confidence: 99%
“…Carbon‐based nanomaterials, such as graphene (GN), graphyne, and heteroatom‐doped carbon materials have been widely adopted as supports for SACs [166–168] . There has been a myriad of studies showing that the metal atoms doped carbon‐based supports can realize significantly enhanced the reaction activities for removal of H 2 S [52,169–172] . However, there are a few reviews works about the interaction between H 2 S and single atom supported catalyst from a theoretical perspective.…”
Section: Single‐atom Catalystmentioning
confidence: 99%
“…Sulfur poisoning widely occurred in catalysts, especially in hydrogen production. Produced hydrogen may contain sulfur from the conversion of fossil fuels and waste gas reformation. The mechanism of sulfur poisoning is that sulfuric compounds are absorbed on the catalytic surface and compete with the active site, which leads to lower catalytic activity . SO 2 contains a strong deactivation effect by adsorption on the catalysts under 150 °C to noble metals, except Pt .…”
Section: Challenges In the Chc Processmentioning
confidence: 99%
“…It is interesting that tetravalent metal ions improve the catalytic performance of zeolites by means of isomorphous substitution into the tetrahedral sites of zeolite. , The local coordinated environment around the metal-incorporated site has a great influence on the structure and acidity of zeolite and hence on the catalytic performance. For example, Curet-Arana et al reported that the incorporation of Sn into BEC and BEA frameworks results in more structural distortion than that of Ti and Ge . If the relationships between the structural properties (e.g., acidity, cell volume, band gap, etc.)…”
Section: Introductionmentioning
confidence: 99%